Kisah Israiliyat Dan Pandangan Ulama Dalam Memahami Tafsir Al-Qur'an - fauziyah hilmi (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2017)
The story of Israiliyyat can not be released with the condition of all societies where the original and complete information becomes the information sought and used as a grip in every human life. In the meantime, ancient societies took the basis through the story of Israiliyyat to get a complete picture of the chronology of every good news brought by the prophets and earlier scholars to be the perfect message for his followers. Sometimes humans experience the turmoil because they do not know exactly how the story is emerging, so gradually people want to take a message that was found in a book scribe who knew about the chronological stories that occurred in the past that is difficult to find an accurate source. There are many stories that have no basis which can explain precisely much less in understanding the Qur'anic interpretation, therefore the story derived from the Jewish scribe provides a thorough illustration although not entirely true.